Age and Appearance Shape Behavioral Responses of Phasmids in a Dynamic Environment - Pohl, Sebastian; Bungum, Haaken Z.; Lee, Kenneth E. M.; Sani, Mohamad Azlin Bin; Poh, Yan H.; Wahab, Rodzay bin Hj Abd; Norma-Rashid, Y.; Tan, Eunice J. (Frontiers in Ecology and Evolution, 2022)
Although morphological adaptations leading to crypsis or mimicry have been studied extensively, their interaction with particular behaviors to avoid detection or recognition is understudied. Yet animal behaviors interact with morphology to reduce detection risk, and the level of protection conferred likely changes according to the surrounding environment. Apart from providing a locational cue for predators, prey motion can also serve as concealing behavior in a dynamic environment to prevent detection by potential predators or prey. Phasmids are conventionally known to rely on their adaptive resemblance to plant parts for protection, and this resemblance may vary across life stages and species. However, little is known about how their behaviors interact with their appearance and their environment. We investigated two species of phasmids with varying morphology and color patterns at different ontogenetic stages and examined their behavioral responses to a wind stimulus as a proxy for a dynamic environment. While adult behaviors were mostly species-specific, behavioral responses of nymphs varied with appearance and environmental condition. Display of different behaviors classified as revealing was positively correlated, while display of concealing behaviors, with the exception of swaying, was mostly negatively correlated with other behaviors. Exhibition of specific behaviors varied with appearance and environmental condition, suggesting that these behavioral responses could help reduce detection or recognition cues. We discuss the differences in behavioral responses in the context of how the behaviors could reveal or conceal the phasmids from potential predators. Our results provide a novel investigation into adaptive resemblance strategies of phasmids through the interaction of behavior and morphology, and highlight the importance of considering the effects of dynamic environments on sending and receiving cues.